Relations of masculinity and femininity with personality dimensions of the five-factor model. - Marušić, Iris; Bratko, Denis (1998)
The aim of this study was to examine the relations of masculinity and femininity with five-factor personality dimensions in Croatian adolescents. Sample consisted of 464 high school graduates, all of them Caucasian, and approximately 90% Croatian. Results were analyzed by multiple regression procedure using masculinity, femininity, gender and their interactions as independent variables. All three main effects were found to be statistically significant, with no significant interactions. Masculinity is contributing positively to extraversion and conscientiousness, and negatively to neuroticism and agreeableness, while femininity shows strong positive relationship with agreeableness, and weak positive relationships with the other four dimensions. Results are discussed in terms of four proposed models of the relation between gender-role orientation and psychological health.
Projekt MZOS
ENG